The Influence of the Knowwantlearned (KWL) Strategy on the Tenthgrade Students’ Reading Comprehensionof Recount Textat Sma Santo Yoseph Medan - Anna Mariani; Meikardo Samuel Prayuda; Fiber Yun Almanda Ginting (Sean Institute, 2026)
This study looked at how the Know-Want-Learned (KWL) approach affected the tenth grade students at SMA St. Yoseph Medan's reading comprehension of recount texts throughout the 2025–2026 school year. The study was carried out because many students continued to struggle with comprehending recount narratives, including recognizing key concepts, understanding specific details, organizing event sequences, and deciphering the text's meaning. Additionally, during the learning process, pupils demonstrated little enthusiasm and minimal participation. This study used a quantitative methodology and a quasi-experimental design, with 58 students split into two groups of 29 students each: an experimental class and a control class. Validity, reliability, normality, homogeneity, and Mann-Whitney U tests were used to assess the data, which were gathered using pre-test and post-test equipment. The reliability analysis revealed that the instrument was dependable with a Cronbach's Alpha score of 0.699, while the validity analysis demonstrated that every test item was legitimate. Additionally, there was a significant difference between pupils taught using the KWL strategy and those taught using traditional teaching methods, as indicated by the Mann-Whitney U test result of 0.001, which was less than 0.05. Additionally, the effect size computation showed a moderate influence with a Cohen's d value of 0.66. Consequently, the results indicated that the KWL approach had a favorable and noteworthy impact on students' comprehension of recount texts and may be employed as a successful teaching method for reading comprehension .